USE OF ADVANCED PEDAGOGICAL TECHNOLOGIES IN TEACHING SCIENCE IN PRIMARY SCHOOL - Dilbar Kadirova Normo‘Minovna; Donaxol Xoliyorova Nomoz Qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article deals with the use of advanced pedagogical technologies in teaching science in elementary school, the requirements for the selection and distribution of educational materials in the classroom, the educational process at school and the content of the studied material. described.